Anti epileptic activity of ocimum species: A brief review - Agarwal, Chhaya; Sharma, N. L.; Gaurav, S. S. (International Journal of Applied Sciences and Biotechnology, 2013)
The Ocimum species is a medicinal herb used in the indigenous system of medicine. Ocimum sp. have variety of biological, pharmacological properties such as antibacterial, antiviral, antifungal, antimalarial, anthelmentic, antidiarrhoeal, antiinflammatory, antihypertensive, cardioprotective, central nervous system (CNS) depressant, antidiabetic, antithyroidic, antioxidant, anticancer, chemopreventive, radioprotective, immunomodulatory, antifertility, antiulcer, antiarthritic, antistress, antileucodermal and anticoagulant activities. Sevral species of Ocimum are used to cure central nervous system (CNS) disorders.in various part of the world due to its anticonvulsant property .epilepsy is a chronic disorder which is characterized by seizures. Seizures are resistant to treatment with currently available anticonvulsant drug (AEDs) in about one out of three patient with epilepsy. This review refers to the study of ocimum as an antiepileptic drug (AEDs) because of its specific anticonvulsant property. DOI: http://dx.doi.org/10.3126/ijasbt.v1i4.9168 Int J Appl Sci Biotechnol, Vol. 1(4): 180-183